IL-4 abrogates TH17 cell-mediated inflammation by selective silencing of IL-23 in antigen-presenting cells - Guenova, Emmanuella; Schäkel, Knut (Proceedings of the National Academy of Sciences of the United States of America, 2015)
Interleukin 4 (IL-4) has been shown to be highly protective against delayed type hypersensitivity and organ-specific autoimmune and autoinflammatory reactions in mice and humans, but its mode of action has remained controversial and has failed to be explained solely by redirection of TH1/TH17 toward a TH2-type immune response. Here we uncovered that IL-4 selectively suppresses IL-23 transcription and secretion by cells of the innate immune system. We further describe a previously unidentified therapeutic mode of action of IL-4 in TH17-mediated inflammation, and a physiologically highly relevant approach to selectively target IL-23/TH17-dependent inflammation while sparing IL-12 and TH1 immune responses., Interleukin 4 (IL-4) can suppress delayed-type hypersensitivity reactions (DTHRs), including organ-specific autoimmune diseases in mice and humans. Despite the broadly documented antiinflammatory effect of IL-4, the underlying mode of action remains incompletely understood, as IL-4 also promotes IL-12 production by dendritic cells (DCs) and IFN-γ-producing TH1 cells in vivo. Studying the impact of IL-4 on the polarization of human and mouse DCs, we found that IL-4 exerts opposing effects on the production of either IL-12 or IL-23. While promoting IL-12-producing capacity of DCs, IL-4 completely abrogates IL-23. Bone marrow chimeras proved that IL-4-mediated suppression of DTHRs relies on the signal transducer and activator of transcription 6 (STAT6)-dependent abrogation of IL-23 in antigen-presenting cells. Moreover, IL-4 therapy attenuated DTHRs by STAT6- and activating transcription factor 3 (ATF3)-dependent suppression of the IL-23/TH17 responses despite simultaneous enhancement of IL-12/TH1 responses. As IL-4 therapy also improves psoriasis in humans and suppresses IL-23/TH17 responses without blocking IL-12/TH1, selective IL-4-mediated IL-23/TH17 silencing is promising as treatment against harmful inflammation, while sparing the IL-12-dependent TH1 responses.